Conceptual Model for Managing Sources of Danger in the Event of an Earthquake - Akimbayev, Yernar; Salhanov, Yerhat; Satbekov, Didar S; Ramazanov, Nurzhan; Kaizer, Tatyana (Migration Letters, 2023)
Safety is a state of human activity in which the realization of a potential danger is excluded with a certain probability. However, there is an axiom: any human activity is potentially dangerous. The criterion, i.e. a quantitative assessment of the danger, is the risk. Practice shows that the previously applied concept of safety, which excluded any manifestations of danger (the concept of zero risk) turned out to be untenable. Currently, the basic concept of security is the concept of justified risk, i.e. risk that, given the available economic opportunities and social relations, is considered acceptable for ordinary citizens. This study presents the results of a conceptual model - a model of communication channels obtained as a result of system analysis and reflecting the dynamics of information flows about the state of sources of danger in the zone of a possible earthquake. The conceptual model consists of functional operators B1, B2, B3, B4, B5, B6, B7. This study is an important direction for improving the effectiveness of protective measures is the mathematical modeling of emergencies and forecasting their consequences.